Cryptochloa stapfii (Poaceae: Bambusoideae: Olyreae), a new neotropical herbaceous bamboo from Panama - Baldini, Riccardo Maria; Ortiz, Orlando Oriel (Phytotaxa, 2015)
Cryptochloa stapfii, a new herbaceous bamboo species from Panama is described. This new bambusoid grass inhabits semi-shaded lowland forests in Bocas del Toro (Panama) and is related to C. dressleri Soderstr., an endemic species from Panama. This new taxon increases the number of species in Cryptochloa to eight, most of them present in Panama.